Entrepreneurship through acquisition: a scoping review - Alexander Hoffmann; Dominik K. Kanbach; Stephan Stubner (Management Review Quarterly, 2023)
Entrepreneurship through acquisition (ETA) is gaining momentum as a viable alternative to starting a company on one's own. However, despite its growing practical relevance, scholarly work about ETA is scarce and has not been comprehensively reviewed. To address this gap, we conduct a systematic review of entrepreneurship literature by identifying studies that examine ETA and its outcomes. Our review methodology was developed based on established guidelines for systematic reviews and protocols, which informed our scoping review process and analytical approach. Searches were conducted on three electronic databases, and inclusion/exclusion criteria were applied. For inclusion, studies must examine an entrepreneurial perspective in buying into a company. Quantitative and qualitative data were extracted for thematic analysis and descriptive statistics. ETA is an entrepreneurship model with growing appeal and relevance in practice but limited academic evidence. While there is extensive research on leveraged buyouts and family-external succession, evidence specifically on ETA is still lacking. In particular, knowledge about the entrepreneurial intent that makes ETA unique is absent from the evidence base. As ETA gains momentum, entrepreneurs need to understand the unique properties, the various approaches, and the upsides and eventual downsides of acquiring a business instead of starting one from scratch. The present work may serve as a starting point for future research as we scope existing evidence on the archetype of ETA and identify a definition, available models, and a process archetype.
Keywords: 650; Entrepreneurship through acquisition; Succession; Buy-outs; Buy-ins; Search funds; Business takeover; Mode of entry